PWE-128 The Out-of-Hours Gastrointestinal Bleed Service in South-West London: A Model for Regional Emergency Endoscopy Cover. (17th August 2016) - Alexakis, C; Chhaya, V; Sutherland, I; Lalani, R; Tavabie, O; Hewett, R; Chan, D; Amarasinghe, G; Ryan, J; Uppal, S; Inayet, N; Woodhouse, C; et al.
Abstract : Introduction: Gastrointestinal (GI) bleeding is associated with a mortality of 10–30%. An NCEPOD report recently recommended that management of GI bleeds should be directed by a named GI bleed clinician, although wasn't implicit that procedures be performed by a consultant. 1 In SW London, 5 hospitals developed a network service to cover out-of-hours emergency endoscopy requirements for the region. It is a registrar-delivered, consultant-supported service. We present the key service outputs over a 10 month period in 2015. Methods: OGDs were performed by registrars accredited with appropriate skills in upper endoscopy. Endoscopists prospectively collected data on all out-of-hours OGDs performed including age and sex of patient, Rockall score, time to OGD, primary endoscopic findings and therapeutic intervention. Data on mortality and re-bleed rates were retrospectively collected for the last 2 months of the study. Results: 172 out-of-hours OGDs were performed between March and December 2015. 57% occured during the weekend, giving rise to a procedure rate of 1.12 OGD/weekend day and 0.33 OGD/week day. Mean age of patient was 59.5 years (range 16–94). 64% were male. Median Rockall score was 4. Mean time to OGD was 4hrs 15 mins (range 1 hr-16hrs). Table 1 shows the primary pathologies at OGD. Therapeutic intervention was needed in 52% of cases. Failure to achieve haemostasis endoscopically occured in 1.7%. Consultant assistance was required in 3 cases. Data from Nov to Dec 2015, which included 40 OGDs (mean age 59 years, 63% males, intervention rate 53%) indicated an inpatient re-bleed rate of 10% (NCEPOD audit rate 23%), an interventional radiology requirement in 6% (NCEPOD 8%) and a surgical intervention rate of 2.5% (NCEPOD 6%). All-cause 30 day mortality rate was 15%, although only one patient (2.5%) died as a direct result of uncontrolled bleeding. Conclusion: The results indicate that an effective and safe regional out-of-hours emergency GI bleed service can be provided via a registrar-delivered, consultant-supported model. This has important implications when considering the development of consultant on-call rosters, and maximising training opportunities for registrars. Reference: 1 NCEPOD 'Time to get control' – a review of the care received by patients who had a severe gastrointestinal haemorrhage 2015. Disclosure of Interest: None Declared